Using a Co-design Approach to Create Tools to Facilitate Physical Activity in Children With Physical Disabilities - Bolster, Eline A. M.; Gessel, Christa van; Welten, Maxime; Hermsen, Sander; Lugt, Remko van der; Kotte, Elles; Essen, Anita van; Bloemen, Manon A. T. (Frontiers in Rehabilitation Sciences, 2021)
Introduction There is a lack of effective interventions available for Pediatric Physical Therapists (PPTs) to promote a physically active lifestyle in children with physical disabilities. Participatory design methods (co-design) may be helpful in generating insights and developing intervention prototypes for facilitating a physically active lifestyle in children with physical disabilities (6 - 12 years). Materials and methods A multidisciplinary development team of designers, developers, and researchers engaged in a co-design process – together with parents, PPTs, and other relevant stakeholders (such as the Dutch Association of PPTs and care sports connectors). In this design process, the team developed prototypes for interventions during three co-creation sessions, four one-week design sprints, living-lab testing and two triangulation sessions. All available co-design data was structured and analyzed by three researchers independently resulting in themes for facilitating physical activity. Results The data rendered two specific outcomes, 1) knowledge cards containing the insights collected during the co-design process, and 2) eleven intervention prototypes. Based on the generated insights, the following factors seem important when facilitating a physically active lifestyle: a) stimulating self-efficacy; b) stimulating autonomy; c) focusing on possibilities; d) focusing on the needs of the individual child; e) collaborating with stakeholders; f) connecting with a child’s environment; and g) meaningful goal setting. Conclusion This study shows how a co-design process can be successfully applied to generate insights and develop interventions in pediatric rehabilitation. The designed prototypes facilitate the incorporation of behavioral change techniques into pediatric rehabilitation and offer new opportunities to facilitate a physically active lifestyle in children with physical disabilities by PPTs. While promising, further studies should examine the feasibility and effectivity of these prototypes. easibility and effectivity of these prototypes.